Non-White Poverty and Macroeconomy: The Impact of Growth - Hoover, Gary A; Enders, Walter; Freeman, Donald G (American Economic Review, 2008)
Although poverty research has a very long history in the social sciences, serious debate on the sufficiency of economic growth to eliminate poverty was rekindled by the inception of the “War on Poverty” by the Kennedy and Johnson Administrations during the early 1960s. Forty years later, the measurement of growth’s effect on poverty remains an important input to the policy question of whether, how much, and how govern ment efforts should address poverty reduction. Early work by Henry J. Aaron (1967) found that poverty among certain groups seemed highly sensitive to economic growth, while other groups were barely affected. Subsequent researchers have realized that poverty has a spa tial as well as a demographic dimension, and more recent work has examined poverty by “race and region” using disaggregated time series. The present study further refines the examination of poverty by racial/ethnic group and region by investigating the impact of economic progress on poverty across black, Hispanic, and white populations measured over 35 years at the level of the census region. To our knowledge, this is the first research to study all three of these groups using regional data. A regional analysis is important because the North, Midwest, South, and West have had different industrial structures and different economic histories over the last three decades. As shown in Figure 1, regional poverty rates of blacks and Hispanics relative to whites are quite different. Moreover, regional differences exist in the levels and growth rates of real per capital GDP, in the secular decline in manufac turing, and in the pattern of the unemployment rate. In addition to economic events, we control Non-White Poverty and Macroeconomy: The Impact of Growth